Online Community Learning: Why Does (Language) Learning without Classroom Interest Students of All Disciplines? A Case Study - Arul Prabaharan Gaspar (Intelektual Pustaka Media Utama, 2017)
This case study explores the language learners’ growing interest to express their shared interest in online-course-providing platforms. This study also inquires into the language learners’ new forum called “online community” and its great influence on smart way teaching-learning process and classroom dynamics, technology enabled lifelong self study mode of learning, subject knowledge, learning centred curriculum, experience centred approach to the learning process, course material and soft/life skills delivered along the course as a value added package. This paper examines the way MOOCs have opened the gate way of learning to all sections of society free of cost with specific language skills focus – writing that interests students from all disciplines. This study suggests that the rising generation shows a growing, academic interest in online collaboration on the basis of any subject specific shared interest and this collective interest also addresses the concern about personal experiences with emotive foundation that will not have space in online teaching learning process.